Histochemical and immunohistochemical evaluation of primary and recurrent pterygium - Kochmanovska-Petrevska, S.; Spasevska, L; Ilievski, B.; Celeva Markovska, V. (My University, 2011)
Objective: Pterygium is benign, fibro vascular and infiltrative process of the conjunctiva of unknown pathogenesis. Histochemical and immunohistochemical. analysis of primary and recurrent pterygium. Method: Histochemical and immunohistochemical analysis of pterygium tissue were done after the surgical excision with autotransplaltation method with graft from the superior or inferior temporal bulbar conjunctiva. The patients were divided in 3 groups: 1. Group of 10 patients with primary-stationary pterygium 2. Group of 10 patients with primary-progressive pterygium 3. Group of 10 patients with recurrent pterygium Species of normal conjunctiva (10) were investigated also as a control group. All tissues were subjected to hematoxylin and eosin staining, immunohistochemical analysis using antibodies again EGF-R, vimentin, CD34 and CD 31 and histochemical staining with Van Giesson Elastica. Results: The histological feature of pterygium overgrowth is excessive fibrovascular proliferation and basement membrane (Bowman's membrane) degeneration. All cases present with chronic inflammation reaction. The increased expression of EGFR proteins was present in pterygium. 8 of 10 pterygium express the stains of EGFR in full thickness of epithelium with intensive staining more than in "conjunctiva. CD34 positive cells were expressed in the basal epithelium and peri-vascular endothelium in primary pterygium, but more significant expression was found in recurrent pterygium. Immunoreactivity of vimentin was detected in myofibroblasts in fibrovascular tissues of primary and recurrent pterygium. Markers for vascular endothelial cells as CD31 + are increased in pterygia. Conclusion: Although pterygium management has traditionally involving surgery the understanding of immunohistochemical events underlying pterygium pathogenesis may enable the use of less invasive treatment methods.